LifeSteps: An Evidence-based Health Promotion Program for Underserved Populations - A Community Service Learning Approach - Melanie Austin-McCain (Scholarworks @ WMU, 2015)
Chronic diseases are the most common, costly, and preventable of all health problems in the United States. Chronic diseases represent the leading causes of death and are experienced at higher rates by minority populations (CDC, 2012). Innovative community-based health promotion programs are recommended that meet the diverse needs of underserved populations (Yeary, et al., 2011). LifeSteps is being developed as an evidence-based health promotion program focusing on health and wellness, a domain area defined within the Occupational Therapy Practice Framework (OTPF, 2008). LifeSteps will utilize a client-centered approach to coach individuals in making health behavior changes. Fieldwork and service-learning components are incorporated integrating clinical practice, academic study, and collaboration with community providers. Program evaluation measures based on the Transtheoretical Model (TTM) have been identified to address all phases of program planning. The LifeSteps health promotion program aligns with local, national, and international objectives and addresses the need for programs that meet the diverse needs of underserved populations. Occupational therapists are in a unique position for implementing community-based interventions that promote health and contribute to a healthier society.